Apakah faktor ekonomi masih berelasi dengan kepuasan kerja lansia ? - Jamalludin, Jamalludin; Pitoyo, Agus Joko; Listiyaningsih, Umi (Jurnal Ketenagakerjaan, 2024)
Job satisfaction is influenced by expectations, which vary at different stages of life. This study aims to analyze the relationship between economic and non-economic factors and the job satisfaction of elderly workers. The analysis is based on data from the 2017 Happiness Level Measurement Survey (SPTK), focusing on 3,582 workers aged 50-70 years who are classified as laborers, employees, or staff. The results show that both economic and non-economic factors are significantly related to job satisfaction among elderly workers. Economic factors have a greater impact on job satisfaction than non-economic factors. Key economic factors include wages, the alignment of wages with the intensity of work, and job security. Non-economic factors include the alignment of job roles with workers' interests and skills, as well as overall job comfort. Among economic variables, wages have the strongest influence on job satisfaction—the lower the wage, the lower the job satisfaction. Among non-economic variables, job comfort has the most substantial impact on job satisfaction.